Workshop on Assistance in Curriculum Development “Merdeka Belajar Kampus Merdeka” at Nahdlatul Ulama University, West Kalimantan - Dona Fitriawan; Agung Hartoyo; Edy Yusmin; Ade Mirza; Nurfadilah Siregar; Revi Lestari Pasaribu (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
This community service activity began with the collaboration between Tanjungpura University and Nahdhatul Ulama University in West Kalimantan, especially in terms of infrastructure, teaching staff (lecturers) and student management. In responding to the new policy from the Ministry of Education, Culture, Research, and Technology regarding the MBKM policy, a new curriculum development policy was made which was closely related to the ministry's policy. This form of service is a workshop or training on